Evaluation of an Antimicrobial Stewardship Program for Wound and Burn Care in Three Hospitals in Nepal - Varidhi Nauriyal; Shankar Man Rai; Rajesh Dhoj Joshi; Buddhi Bahadur Thapa; Linda Kaljee; Tyler Prentiss; Gina Maki; Basudha Shrestha; Deepak C. Bajracharya; Kshitij Karki; Nilesh Joshi; Arjun Acharya; et al. (Antibiotics, 2020)
Antimicrobial stewardship (AMS) programs can decrease non-optimal use of antibiotics in hospital settings. There are limited data on AMS programs in burn and chronic wound centers in low- and middle-income countries (LMIC). A post-prescription review and feedback (PPRF) program was implemented in three hospitals in Nepal with a focus on wound and burn care. A total of 241 baseline and 236 post-intervention patient chart data were collected from three hospitals. There was a significant decrease in utilizing days of therapy per 1000 patient days (DOT/1000 PD) of penicillin (p = 0.02), aminoglycoside (p < 0.001), and cephalosporin (p = 0.04). Increases in DOT/1000 PD at post-intervention were significant for metronidazole (p < 0.001), quinolone (p = 0.01), and other antibiotics (p < 0.001). Changes in use of antibiotics varied across hospitals, e.g., cephalosporin use decreased significantly at Kirtipur Hospital (p < 0.001) and Pokhara Academy of Health Sciences (p = 0.02), but not at Kathmandu Model Hospital (p = 0.59). An independent review conducted by infectious disease specialists at the Henry Ford Health System revealed significant changes in antibiotic prescribing practices both overall and by hospital. There was a decrease in mean number of intravenous antibiotic days between baseline (10.1 (SD 8.8)) and post-intervention (8.8 (SD 6.5)) (t = 3.56; p < 0.001), but no difference for oral antibiotics. Compared to baseline, over the 6-month post-intervention period, we found an increase in justified use of antibiotics (p < 0.001), de-escalation (p < 0.001), accurate documentation (p < 0.001), and adherence to the study antibiotic prescribing guidelines at 72 h (p < 0.001) and after diagnoses (p < 0.001). The evaluation data presented provide evidence that PPRF training and program implementation can contribute to hospital-based antibiotic stewardship for wound and burn care in Nepal.